Low level of physical fitness is an early feature in preschool children with autism (El nivel bajo de la aptitud física es una característica temprana en niños preescolares con autismo) - Pedro Ángel Latorre Román; Míriam Sánchez Salvador; Jesús Salas Sánchez; Felipe García Pinillos (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Background: Physical fitness level is a potent biomarker of health from an early age. Physical activity and Physical fitness have a similar influence on health outcomes including overweight. However, Physical activity and Physical fitness in children with autism spectrum disorders have received little attention. The purpose of this study was to evaluate physical fitness in preschool children with ASD. Methods: A total of 31 children, aged 3 to 6 years, participated in this study: 13 children with ASD (Age=50.23±7.62 months, 2 girls and 11boys) and 18 children without ASD (Age=51.33±11.06 months, 4 girls and 14 boys). A fitness test battery was employed. Results: Children with ASD have lower performance in physical fitness tests. However, no significant differences were found in anthropometrics characteristics, physical activity time, screen-based time and physical functioning. Conclusions: Preschoolers with ASD have an early deterioration in physical fitness. Physical activity programs at pre-school level are necessary to stimulate these abilities in children with ASD.